Isolation and Identification of Thrush Disease in Human - Mohammed abdul hameeed Hassan; Walaa Najm Abood (Academic Science Journal)
Background: Candidiasis is the most frequent fungal infection in the oral cavity of human. As a result, they have the potential to trigger an opportunistic infection known as oral Candidiasis. A high percentage of healthy persons have commensals Candida in their oral cavity with or without signs or symptoms of Candidiasis. Candida overgrowth is enhanced by many predisposing factors such as immunological status of the patient, heredity, and malignant tumors. The purpose of this study was to isolate Candida albicans from oral candidiasis patients by using Sabouraud's Dextrose agar medium and performing preliminary differentiating of Candida albicans and other yeasts according to NICKERSON and its connection with oral mucosal diseases. Fifty samples of infected human (male) with clinically confirmed oral mucosal lesions were collected and 22 samples of human (male) with no symptoms were collected (control). Candida spp growth was detected using SDA in (26 out of 50) patients with a (52%) isolate from 50 (100%) samples. Candida albicans was diagnosed in 10 (45.5%) isolate from twenty-two sample (control group), whereas 24 (48%) were isolated from 50 sample on candida elective agar. In conclusion, Candida albicans was, among other Candida spp. that causes thrush illness in human.